Marginal notes, Zeitgeist and memory of the present time: readers’ comments in cyberjournalism - Palacios, Marcos (Brazilian journalism research, 2012)
This work proposes an application of the concept of Marginal Notes to journalistic texts, and more specifically, their utilization for the characterization of Readers´ Comments in Cyberjournalism as an emerging form of Memory. The concept of Marginal Notes is discussed in its classical sense and then transposed to the situation of journalistic production. The idea of journalistic Marginal Notes is also associated with the topic of the War of the Memories, but what is basically distinguished is the value of the preservation of these comments as possible indicators of a Zeitgeist to be possibly recovered, from a specific historical distance. Some examples of Marginal Notes in journalism in online media are furnished. Attention is called to the need for understanding Marginal Notes as a “text”, in the broad sense of the word, since all the (multi)media formats incorporated as readers´ contributions should be included in the concept, and consequently efforts should be made for their preservation for future uses.